Micro to nano: Surface size scale and superhydrophobicity - Christian Dorrer (Beilstein Journal of Nanotechnology, 2011)
This work looks at the fundamental question of how the surface mobility of drops in the composite state is related to the size scale of the roughness features of the surface. To this end, relevant literature is first reviewed and the important terms are clarified. We then describe and discuss contact and roll-off angle measurements on a set of hydrophobicized silicon post surfaces for which all parameters except for the surface size scale were held constant. It was found that a critical transition from “sticky superhydrophobic” (composite state with large contact angle hysteresis) to “truly superhydrophobic” (composite state with low hysteresis) takes place as the size of the surface features reaches 1 μm.